PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK-TALK-WRITE (TTW) TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS VIII SMP NEGERI 3 PADANG - DWI FADILLAH PUTRI (Jurnal Edukasi dan Penelitian Matematika, 2018)
Ability of matematical comunication is one of purpose have must have by student in the learning mathematic. However to reality, student's mathematical communication ability grade VII SMP 3 Padang still low. one of the way improve to it problem is with use cooperative learning model Think-Talk-Write (TTW) type. The aim of this study is to describe if student's mathematical communication ability acquire learning with cooperative learning model Think-Talk-Write (TTW) type better than student acquire study with convensional and student response to cooperative learning model Think-Talk-Write (TTW) type. This type of research is descriptive and quasi-experiment. The instrument use is a mathematical communication ability test and questionnaire. The conclusion based on the analysis of t test is student's mathematical communication ability acquire learning with cooperative learning model Think-Talk-Write (TTW) type better than student acquire study with convensional. Keywords – Mathematical comunication ability, Cooperative learning model Think-Talk-Write (TTW) type, Conventional learning